THE INTERACTION EFFECT OF TEACHING AND LEARNING MOTIVATION TOWARDS THE STUDENT’S ENGLISH RESULT ( AN EXPERIMENT AT STATE JUNIOR HIGH SCHOOL IN BOGOR REGION) - Muhammad Ahsan Tampubolon (Universitas Pamulang, 2019)
Abstract `The purpose of this study was to determine the interaction effect of teaching and learning motivation towards students’ English result consisting of 30 for experiment class and 30 for control class, and the sampling technique used is cluster random sampling. The research was guided by a conceptual framework leading to the two ways of ANNOVA Research instrument used were the test results od learning motivation and English result scoring that have been tested : 1) there is an significant effect of teaching method towards the students’ English score, as Fo = 17,994 and Sig. = 0,000 < 0.05. 2) there is a significant effect of motivation towards students’ English score, as Fo = 31.308 and Sig. = 0.000 < 0.05. 3) there is an interactive significant effect of teaching method and motivation towards the students’ English score, as Fo = 3.858 and Sig. = 0.054 > 0.05. the results contribute most to increasing of the students’ English score by using the Inquiry Method beside reinforcing of the students’ motivation trait in the classroom activity. Keywords: interaction effect, teaching, learning motivation.